Penanganan Penumpang dan Bagasi oleh Petugas Aviation Security dalam Menunjang Keamanan dan Keselamatan Penerbangan YIA - Alberth Paulino Suroso; Herida Panji Olivia Azhar (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Abstract. Handling of passengers and baggage by officers aviation security refers to the process of security checks carried out on passengers and luggage before taking a flight. This study aims to explain how passengers and baggage are handled by officers aviation security at Yogyakarta International Airport and explained how the dynamics faced by officers aviation security in his duties to handle passengers and baggage. This study uses a qualitative descriptive method with data collection techniques through observation in the section security check point for the process of handling passengers and baggage as well as interviews with Performance and Security Coordinator for officers aviation security. The results showed that the handling of passengers and baggage by officers aviation security at Yogyakarta International Airport is fully in accordance with regulation Standard Operational Procedure (SOP). Officer aviation security facing various dynamics in their duties to handle passengers and baggage. Experienced dynamics such as long queues, different security situations and passengers who do not understand flight regulations, especially luggage that violates the rules.